Lithosphere literacy in the knowledge domain of physics education students - Rahmi Zulva; Andi Suhandi; Agus Setiawan; Achmad Samsudin; Indri Sari Utami (Universitas Sultan Ageng Tirtayasa, 2026)
Lithosphere literacy is an important component of scientific literacy for physics education students, particularly in understanding geological phenomena that frequently occur in disaster-prone regions. This study aimed to analyze students’ knowledge across several lithosphere concepts and knowledge types. The research employed a quantitative descriptive approach involving 88 physics education students. The instrument used was a multiple-choice test designed to measure students’ knowledge in the domains of factual, conceptual, and procedural knowledge across four lithosphere concepts: volcanism, earthquakes, liquefaction, and the earth’s magnetic field. Descriptive statistics and correlation analysis were used to examine students’ performance across concepts and knowledge types. The results show that the overall mean score of students’ knowledge was 50.12, indicating a moderate level of understanding. Among the concepts analyzed, the earth’s magnetic field topic obtained the highest average score (51.86), while earthquakes showed the lowest (48.72). In terms of knowledge types, factual knowledge achieved slightly higher scores compared to conceptual and procedural knowledge. Correlation analysis revealed significant positive relationships between knowledge scores across the lithosphere concepts (p < 0.001), suggesting that students’ understanding of one concept is related to their understanding of other concepts. These findings indicate that although students demonstrate relatively balanced knowledge across concepts, further improvement is needed, particularly in strengthening conceptual and procedural understanding. The results highlight the importance of implementing learning approaches that support deeper conceptual engagement and scientific reasoning in lithosphere-related topics.